Post-COVID-19 follow-up clinic: depicting chronicity of a new disease - Rovere Querini, Patrizia; De Lorenzo, Rebecca; Conte, Caterina; Brioni, Elena; Lanzani, Chiara; Yacoub, Mona Rita; Chionna, Raffaella; Martinenghi, Sabina; Vitali, Giordano; Tresoldi, Moreno; Ciceri, Fabio (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: The coronavirus disease-19 (COVID-19) outbreak is posing considerable challenges to healthcare systems and societies worldwide. While the knowledge on the acute phase of the disease has rapidly expanded, little is known on the consequences of COVID-19 following clinical remission. We set up a multidisciplinary COVID-19 follow-up outpatient clinic to identify and address the clinical needs of COVID-19 survivors. Here we describe the features of our follow-up programme. Methods: The multidisciplinary assessment comprises a complete physical examination, respiratory evaluation (peripheral oxygen saturation, respiratory rate, dyspnoea assessment, lung ultrasound and pulmonary function), cardiovascular assessment (electrocardiography, echocardiography), nutritional assessment (anthropometrics, mini Nutritional Assessment screening tool), neurological examination including cognitive tests, and mental health assessment. All data are prospectively collected, and blood is sampled for biobanking. Results: Since 7 April to 5 June, 2020, 453 out of the 1388 COVID-19 survivors managed at our University Hospital have been evaluated at the Outpatient COVID-19 Follow-up Clinic. The characteristics of the follow-up cohort are similar to those of the whole cohort of COVID-19 in terms of demographics, comorbidities, and COVID-19 severity upon ED presentation, indicating that the follow-up cohort is representative of the whole cohort. Conclusions: Continuous patient monitoring might give an answer to the numerous unsolved questions about what comes next in this pandemic and beyond. This will help physicians and researchers establish strategies to face future pandemics and develop preventative and therapeutic strategies for similar hyperinflammatory conditions.